A restraining device to aid identification of bees by digital photography - Thomson, James Douglas; Zung, Jessica Lauren (Journal of Pollination Ecology, 2015)
We developed a simple restraining chamber to hold captured bumble bees temporarily so they could be photographed in the field using inexpensive “point-and-shoot” digital cameras. The process is quick, and the resulting “digital voucher” images allowed us to correct a substantial fraction of field identifications based on visual inspection. The system can improve the accuracy of monitoring programs in which it is undesirable to kill specimens to provide traditional vouchers.